Energy metabolism of growing blue foxes - Koskinen,Nita; Tauson, Anne-Helene; Sepponen, Juhani; Rekilä, Teppo (International Fur Animal Scientific Association (IFASA), 2008)
The blue fox (Alopex lagopus) is presently the most important species in fur farming in Finland. In recent years selective breeding programmes have focused on producing large and heavy animals. Ten years ago the average weight at pelting of blue fox vixens varied between 7 and 10 kg. Nowadays individuals weighing over 20 kg can be found. At present blue foxes are fed ad libitum during the growing - furring period. The blue fox exhibits seasonal fluctuations in feed intake and accretion of body fat, feed intake and body fat retention being very high during autumn and early winter if given free access to feed. Unrestricted feeding hence often leads to animals being very fat or even obese at the time of pelting. The accumulation of body fat may have dual purposes, both of crucial importance for animals living in the wild: first to provide insulation of the body and protection from excessive heat loss when ambient temperature is very low and second, to serve as an energy reserve in situations of scarcity.
Keywords: Ko; turkiseläimet; sinikettu; energia-aineenvaihdunta; kasvu; furbearing animals; energy metabolism; growth; fur animals; blue fox